PERANCANGAN MEDIA PEMBELAJARAN UNTUK MATA PELAJARAN ANIMASI BLENDER KELAS XII SMK KANAAN UNGARAN - Rudjiono, Daniel; Setyo Adi Nugroho; Agus priyadi; Krisna Danu Aji Saputra (UNIVERSITAS STEKOM, 2023)
The aim of this research is to create flash-based animation learning media for students at Kanaan Ungaran Vocational School, as well as increasing students' interest in learning animation. The method used is Research and Development, namely a method that develops a particular product such as animation-based learning media. This research was motivated by the discovery of a lack of media for learning animation at Kanaan Ungaran Vocational School, especially in class XI Multimedia animation lessons. Due to the lack of learning media, this creates students' interest and motivation in learning animation, so the author can conclude that students need a media that can generate learning motivation. The result of this research is an application from Adobe Flash CS6 which is an application that contains interactive animations that can be played by